Vitality Forms Processing in the Insula during Action Observation: A Multivoxel Pattern Analysis - Di Cesare, Giuseppe; Valente, Giancarlo; Di Dio, Cinzia; Ruffaldi, Emanuele; Bergamasco, Massimo; Goebel, Rainer; Rizzolatti, Giacomo (Frontiers in Human Neuroscience, 2016)
Observing how an action is done by others allows the observer to understand the cognitive state of the agent. This information, carried by the kinematics of the observed action, has been defined by Stern “vitality forms”. In the present experiment we presented participants with videos showing hand actions performed with different velocities and asked them to judge their vitality form (gentle, neutral, rude) or their velocity (slow, medium, fast). Previous studies showed that the dorso-central insula is selectively active both during vitality form observation and execution. The aim of the present study was to assess, using multi-voxel pattern analysis (MVPA), whether in the insula there were voxels discriminating vitality form from velocity. Results showed that, consistently across subjects, in the dorso-central sector of the insula there were voxels selectively tuned to vitality forms. These results indicate that the dorso-central insula, which previous data showed involved in the vitality form processing contains voxels specific for the action style processing.